EXAMINING THE CULTURE OF ADHAN AND IQOMAH PREACHING IN NEWBORNS: PERSPECTIVES ON RELIGION AND PSYCHOLOGY - Vachruddin, Vrisko Putra; Rofiq, Arif Ainur; Hidayatulloh, M. Syarif (Journal Analytica Islamica, 2024)
The practice of adhan and iqomah in the ears of newborns has become a culture that melts within the Islamic community in Indonesia. If we look deeper, the concept comes from one of the sources of Islamic law, namely hadith of the Prophet. There is controversy regarding the side of shaykh or the truth of the hadith is a serious problematics responded by Muslim scholars today. The authors sought to explore research and studies related to the concept of adhan and iqomah in newborns through the study of the disciplines of Psychology, Education and Islam. The author describes the study of the article in several study objects: 1. Living Hadith Study on The view of Adhan and Iqomah in Newborns, 2. Relevance of The Concept of Adhan and Iqomah view in Newborns with Psychological and Educational Sciences, 3. Analysis of the text of Qur'anic verses relating to the view of Adhan and Iqomah in Infants. The opinion of the 'Ulama mukharrij hadith, states that the hadith includes hadith Saheeh or Hasan lighoirihi, and punish the hadith is advised or sunnah, but the critics of the hadith states that the hadith Dhaif because of the disconnection of sanad and the practice of the hadith can be done if only virtue charity only. In terms of psychology and education the practice is very well done to give the impact of baby growth in the future.